Identifikasi kesulitan belajar biologi siswa SMA di Kabupaten Kampar - Petria Anugrah; Nurul Fauziah (Universitas Sebelas Maret, 2024)
ENLearning difficulties are inappropriate leraning caused by possible brain dysfunction, difficulty in academic tasks, and low leraning achievement. This research aims to determine the profile of student’s learning biology in class XI SMA Negeri 1 Tambang for the 2022/2023 academic year. This research in descriptive research using quantitative and qualitative approaches. The method used in this research is a survey method with collectioncarried aot through interview and qustionnaires. Sampling used a saturated sampling technique. The sample in this study was 120 class XI sciense students. The data analysis technique uses quantitative descriptive. The questionnaire distributed consisted of 4 indicators with 32 statements. The results of the research revealed that the biology learning difficulty profile of class moderate, the community environmental indicators is 81,4 in the very high category. Based on the research results, it can be concluded that the profile of sudents’ learning difficulties in leraning biology in class XI SMA N egeri 1 Tambang for the 2022/2023 academic year is vey high with a percentage of 78.9%IDKesulitan belajar merupakan ketidak tepatan pembelajaran yang disebabkan oleh kemungkinan adanya disfungsi otak, kesulitan dalam tugas-tugas akademik, dan prestasi belajar yang rendah, kesulitan belajar ini sering terjadi pada setiap peserta didik karena ada berbagai faktor yang mempengaruhinya. Penelitian ini bertujuan untuk mengetahui Profil kesulitan belajar siswa dalam pembelajaran biologi di kelas XI SMA Negeri 1 Tambang Tahun Ajaran 2022/2023. Penelitian ini adalah penelitian deskriptif dengan menggunakan pendekatan kuantitatif dan kualitatif. Metode yang digunakan dalam penelitian ini metode survei dengan pengumpulan pengumpulan dilakukan melalui wawancara dan angket. Pengambilan sampel menggunakan teknik sampel jenuh. Sampel dalam penelitian ini sebanyak 120 orang siswa kelas XI IPA. Teknik analisis data menggunakan deskriptif kuantitatif. Angket yang disebarkan terdiri dari 4 indikator dengan 32 pernyataan